Does Intellectual Capital Spur Sustainable Competitive Advantage and Sustainable Growth?: A Study of Chinese and Pakistani Firms. (February 2021) - Lu, Yuqiu; Li, Guowei; Luo, Zhe; Anwar, Muhammad; Zhang, Yunju
Steered by the resource-based view theory, this study scrutinizes the impact of the dimensions of Intellectual Capital (IC)—human capital, structural capital, and relational capital (RC)—on sustainable growth (SG) with the mediating role of Sustainable Competitive Advantage (SCA). We gathered data from 2010 to 2017 of 90 listed firms of China and Pakistan, respectively, and applied EVIEWS. The results indicate that IC plays a significant role in the SG of Chinese and Pakistani firms. IC has a significant influence on differentiation strategy (DS) in Chinese firms whereas only RC has an insignificant influence on DS in Pakistani firms. IC has a significant influence on cost leadership strategy (CLS) in Pakistani firms whereas structural and RC have an insignificant influence on the SG of Chinese firms. In terms of the mediating role, DS partially mediates the relationship between IC and SG in Pakistani firms while it only fully mediates the path between RC and SG in Chinese firms. CLS partially mediates the relationship between IC and SG in Chinese firms while it fully mediates the association between human capital and SG in Pakistani firms. This study recommends Chinese and Pakistani firms to encourage investment in IC to gain SCA and SG in the turbulent markets. To concise, this research advises Chinese firms to invest a satisfactory amount in human capital as compared with structural and RC. However, Pakistani firms should focus on IC to gain SCA and SG.